2021
DOI: 10.3329/bjm.v32i1.51088
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistanceamong Intensive Care Unit Patients in A Tertiary Care Hospital of Bangladesh

Abstract: Background: Antimicrobial resistance is a growing concern specially among the critically ill patients who are often treated by multiple antibiotics. But, the data regarding the pattern of antimicrobial resistance in this population are often insufficient. Objective: To observe the pattern of antimicrobial resistance among the patients admitted into the intensive care unit (ICU). Methodology: This prospective observational study was carried out in the ICU of a tertiary care hospital of Bangladesh ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
3
8
0
Order By: Relevance
“…According to our ndings, the most common isolates associated with the transmission of germs by pus samples were Pseudomonas spp., followed by Enterococcus faecalis, E. coli, and Proteus spp. These ndings have been veri ed by additional studies [18,19]. In this study, Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to our ndings, the most common isolates associated with the transmission of germs by pus samples were Pseudomonas spp., followed by Enterococcus faecalis, E. coli, and Proteus spp. These ndings have been veri ed by additional studies [18,19]. In this study, Pseudomonas spp.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, Pseudomonas spp. made up 58.69% of the gram-negative bacteria, and Enterococcus faecalis made up roughly 39.02% of the gram-positive bacteria [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…13,28 Our study is slightly dissimilar with the finding of Jesmin et al in Bangladesh (Amikacin 28.57%, Gentamicin 14.29%, Meropenem 50%); Khan et al India Amikacin 40%, Meropenem 48% ) respectively. 29,21 The second prevalent organism, Klebsiella pneumoniae, shows the highest sensitivity towards Colistin and Ertapenem (100%, respectively), followed by Imipenem and Meropenem (40%, respectively). These findings were nearly comparable with other studies by Fatema et 17,29 The most effective drugs for Gram-positive were Linezolid.…”
Section: According To Grammentioning
confidence: 99%
“…29,21 The second prevalent organism, Klebsiella pneumoniae, shows the highest sensitivity towards Colistin and Ertapenem (100%, respectively), followed by Imipenem and Meropenem (40%, respectively). These findings were nearly comparable with other studies by Fatema et 17,29 The most effective drugs for Gram-positive were Linezolid. Other susceptible drugs against Grampositive bacteria were Vancomycin and Tigecycline.…”
Section: According To Grammentioning
confidence: 99%
“…Studies conducted in many developing nations, including Africa, Ethiopia, Nigeria, and Ghana, have shown that the presence of AMR and MDR reduces the effectiveness of treatments for common wound infections [ 15 , 16 ]. Thus, the development of AMR and MDR leads to therapeutic failure, prolonged hospitalization, increased treatment cost, mortality, and the spread of MDR pathogens [ 17 ].…”
Section: Introductionmentioning
confidence: 99%